A Dynamic Equilibrium Analysis of a Carbon Tax - Brita Bye (Statistics Norway, Research Department, 1995)
This paper analyses the effects of a carbon tax on a small open petroleum producing economy, using an aggregate intertemporal general equilibrium model with differentiated products. The long run effects on welfare and capital accumulation of both a unilateral and an international carbon tax are emphasised. It is shown that the steady state welfare effect of a carbon tax can be positive or negative, depending on substitution effects which create efficiency losses, and income effects from changes in terms of trade. The presence of an initial tax wedge implies that there is an ambiguous relationship between the tax level and steady state welfare. With an international carbon tax the terms of trade gain is smaller and the petroleum revenue is reduced compared to a unilateral carbon tax, implying that for a petroleum producing economy an international carbon tax may be less beneficial than a unilateral carbon tax.
Keywords: D50; D60; D90; Q43; 330; Dynamic equilibrium analysis; Differentiated products; Carbon taxes.